پاکستان میں تحریک احمدیت کی اپنے تعلیمی اداروں کے ذریعے تبلیغ: Propagation of Ahmadiyya Movement through its Educational Institution in Pakistan (Al-Qamar, 2022)
Ahmadiyya is a religion-socio-political movement that originated in the late 19th century in India during British control. It was founded by Mirza Ghulam Ahmad (1835–1908), who claimed to be the "Promised Messiah" and "Mahdi" awaited by various Islamic traditions. Ahmadies self-identify them as a Muslims but Muslim community does not consider the followers of Ahmadism as their part due to their deviation from the belief of Islam. Ahmadis believe that Ghulam Ahmad was a reformer and spiritual leader sent by God to renew and restore the true teachings of Islam. In this article we see that the Ahmadiyya educational institutions are schools and universities that are associated with the Ahmadiyya Muslim community. These institutions are established to provide education to members of the community as well as to the broader society. Just like other religious communities, the Ahmadiyya community places a strong emphasis on education as a means of personal and societal development. This institution propagation the Muslim faith through education. In this paper it clear that Muslim should not deceived by the word Ahmad, but this institution should be considered as Ahamdi/Qadyani institution.
Keywords: Ahmadiyya; Mirza Gulam Ahmad; Education; Muslim